Controlled decoration of the surface with macromolecules: polymerization on a self-assembled monolayer (SAM)1. (21st May 2015) - Murugan, P.; Krishnamurthy, Munusamy; Jaisankar, Sellamuthu N.; Samanta, Debasis; Mandal, Asit Baran
<x xml:space="preserve">Abstract</x> Various methods of functionalization of surfaces with polymers and their applications have been critically reviewed.